The collected works of Lcaṅ-luṅ Pandi-ta Ṅag-dbaṅ-blo-bzaṅ-bstan-paʼi-rgyal-mtshan - Ṅag-dbaṅ-blo-bzaṅ-bstan-paʼi-rgyal-mtshan, Lcaṅ-luṅ Paṇḍi-ta, 1770-1846 (Mongolian Lama Gurudeva, 1975)
Collected Tibetan works of an Inner Mongolian Lama from the Abaga area and belonging to the Gelukpa tradition.